TiO2 Crystallization at Room Temperature and Preparation of Transparent Carbon Counter Electrode for Low-Cost Dye-Sensitized Solar Cells - Syauqi, Muhammad Iqbal; Sanjaya, Afiten Rahmin; Madiabu, Mohammad Jihad; Khalil, Munawar; Gunlazuardi, Jarnuzi (Makara Journal of Science, 2023)
We developed a low-cost dye-sensitized solar cell (DSSC) using TiO2 fabricated via rapid breakdown anodization (RBA) and ultrafast room-temperature crystallization (URTC). The prepared TiO2 was deposited on a self-made fluorine-doped tin oxide (FTO) conductive glass, and the FTO/TiO2 system was sensitized using curcumin dye. The DSSC was constructed by sandwiching the FTO/TiO2/curcumin electrode with an I−/I2 electrolyte and a transparent carbon counter electrode prepared using a liquid–liquid interface system. The characterization results showed that the TiO2 freshly prepared via URTC was transformed into an anatase crystalline phase, which exhibited a 3.10 eV band gap and a 10.08 nm average crystallite size, comparable to those of the TiO2 prepared via the conventional 450 °C annealing treatment (3.13 eV, 11.60 nm). The photocurrent activity of the URTC-prepared TiO2 under ultraviolet light (0.10 mA/cm2) was also comparable to that of the annealed TiO2 (0.12 mA/cm2). In addition, a transparent carbon electrode (FTO/Ct) was prepared successfully; it exhibited a ±58.26% transparency under visible light and comparable electrocatalytic activity to Pt-coated FTO. The DSSC based on FTO/TiO2-URTC/curcumin and FTO/Ct showed front and back illumination efficiencies of 0.47% and 0.26%, respectively. These results are only slightly lower than those of the conventional DSSC with FTO/annealed TiO2/curcumin//FTO/Pt, which exhibited front and back illumination efficiencies of 0.52% and 0.36%, respectively.